A REVIEW: ANTI-ULCER POTENTIAL - Singh, Charanjeet; Gujar, Bhojraj; Sharma, Yogesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2019)
Peptic ulcer occurs due to an imbalance between the aggressive (acid, pepsin and Helicobacter pylori) and the defensive (gastric mucus and bicarbonate secretion, prostaglandins, innate resistance of the mucosal cells) factors. Gastric ulcers are usually single and less than 2 cm in diameter. A minority of patients with gastric ulcers exhibit acid hyper secretion. In these persons, the ulcers are usually near the pylorus and are considered variants of duodenal ulcers. Several minutes after food enters the stomach, gentle, rippling, peristaltic movements called mixing waves pass over the stomach every 15 to 25 seconds. These waves macerate food, mix it with secretions of gastric glands and reduce it to a soupy liquid called chyme. Proton pumps powered by H+ / K+ ATPase actively transport H+ into the lumen while bringing potassium ions (K+) into the cells. At the same time Cl- and K+ diffuse out through Cl- and K+ channels in the apical membrane. One of the most interesting substances that has been obtained from chilly peppers and present in spicy plants such as ginger or black pepper is capsaicin. This substance acts on sensory neurons to stimulate their membrane receptors, predominantly vaniloid (VR)-1 receptors, and release various kinins such as substance P. Chamomile also may be effective in relieving inflamed or irritated mucous membranes of the digestive tract and in promoting digestion. The plant part of C. sativus like Ripe raw fruits are said to cure spure and in Indo-China cook immature fruits are given to children to treat dysentery. The seed is cooling, diuretic, tonic and anthelmintic. Seeds are used as taeniacide. The leaf juice is used to treat dyspepsia in children. Leaves along with cumin seeds are administered for throat infection. A decoction of root is diuretic. Keywords: Gastric ulcers, Peptic ulcer, C. sativus, Anti-ulcer.